2007
DOI: 10.1002/ijc.22565
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in one‐carbon metabolism and trans‐sulfuration pathway genes and susceptibility to bladder cancer

Abstract: We have previously reported significant inverse associations between bladder cancer risk and dietary intake of vitamins B2, B6, B12, folate and protein in a hospital-based bladder cancer case-control study conducted in Spain (1,150 cases;1,149 controls). Because these dietary factors are involved in the one-carbon metabolism pathway, we evaluated associations between bladder cancer risk and 33 single nucleotide polymorphisms (SNPs) in 8 genes (CBS, CTH, MTHFR, MTR, MTRR, SHMT1, SLC19A1 and TYMS) and interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 27 publications
(46 reference statements)
2
50
0
Order By: Relevance
“…The SHMT1 1420T allele was associated with elevated plasma and RBC levels of folate in one (59) but not another study (60). In studies of associations with cancer risk, the SHMT1 1420T allele was reported to be associated with reduced risk of acute lymphocytic leukemia (58) and malignant lymphoma (61), but null findings have been reported for colorectal (60), bladder (62), breast (48), lung (63), and ovarian cancers (64). In the absence of a phenotypic effect of SHMT1 C1420T, and given the generally null findings of dietary and blood level studies with regard to vitamin B6 (8, 9, 11, 13), our result could be attributable to chance.…”
Section: Discussionmentioning
confidence: 99%
“…The SHMT1 1420T allele was associated with elevated plasma and RBC levels of folate in one (59) but not another study (60). In studies of associations with cancer risk, the SHMT1 1420T allele was reported to be associated with reduced risk of acute lymphocytic leukemia (58) and malignant lymphoma (61), but null findings have been reported for colorectal (60), bladder (62), breast (48), lung (63), and ovarian cancers (64). In the absence of a phenotypic effect of SHMT1 C1420T, and given the generally null findings of dietary and blood level studies with regard to vitamin B6 (8, 9, 11, 13), our result could be attributable to chance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown associations with colon (14), lung (15) and breast cancer (16), and relationships with tumor aggressiveness and variable responses to esophageal cancer treatment (17). Other studies did not confirm associations between the polymorphism and different types of cancer, including colorectal (18), lung (19), bladder (20), and stomach cancer (21).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These studies have focused, primarily, on identifying associations between disease risk and non-synonymous (ns) and previously well-characterized polymorphisms. However, given the number of genes that are involved in the folate pathway (Figure 1), investigation of disease associations with other, less-well investigated genomic loci may be warranted and may uncover new genetic associations.…”
Section: Introductionmentioning
confidence: 99%